2012
DOI: 10.1637/10202-041312-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Italian Field Survey Reveals a High Diffusion of Avian Metapneumovirus Subtype B in Layers and Weaknesses in the Vaccination Strategy Applied

Abstract: The current information on the prevalence of avian metapneumovirus (aMPV) infection in layers is fragmentary and its true impact on egg production often remains unknown or unclear. In order to draw an epidemiologic picture of aMPV presence in layer flocks in Italy, a survey was performed on 19 flocks of pullets and layers based on longitudinal studies or sporadic samplings. aMPV was detected by reverse transcription (RT)-PCR, and blood samples were collected for serology by aMPV ELISA. Occurrences of respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…
nomic losses mainly due to respiratory or reproductive problems (Cecchinato et al, 2012), often exacerbated by secondary bacterial infections (Giovanardi et al, 2014).First, aMPV isolations in Europe date back to the second half of the 1980s, when turkey rhinotracheitis (TRT) outbreaks appeared in
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
nomic losses mainly due to respiratory or reproductive problems (Cecchinato et al, 2012), often exacerbated by secondary bacterial infections (Giovanardi et al, 2014).First, aMPV isolations in Europe date back to the second half of the 1980s, when turkey rhinotracheitis (TRT) outbreaks appeared in
…”
mentioning
confidence: 99%
“…nomic losses mainly due to respiratory or reproductive problems (Cecchinato et al, 2012), often exacerbated by secondary bacterial infections (Giovanardi et al, 2014).…”
mentioning
confidence: 99%
“…In China, a similar disease picture was reported in egg-laying Muscovy ducks [ 63 ]. In Italy, longitudinal studies and sporadic samplings indicated that most pullet flocks get infected with AMPV before the laying begins [ 64 ].…”
Section: Viral Infections That Induce Ovary And/or Oviduct Diseasementioning
confidence: 99%
“…Four aMPV subtypes (A, B, C and D) have been recognized based on nucleotide sequence differences (Gough & Jones, 2008). Subtype B infection has become endemic in densely populated Italian poultry areas since its first detection in the late 1980s (Fabris & D'aprile, 1990;Catelli et al, 2004Catelli et al, , 2010Cecchinato et al, 2012). Live vaccines of subtype B are routinely applied to 1-day-old turkeys to prevent respiratory disease.…”
Section: Introductionmentioning
confidence: 99%